Analisis Komposisi dan Struktur Vegetasi Hutan (Studi Kasus: Taman Wisata Alam Camplong dan Taman Wisata Alam Baumata Kabupaten Kupang) - Ika Krisnawati; Aah Ahmad Almulqu; Adrin Adrin; Emi Renoat (UNIVERSITAS PGRI MADIUN, 2022)
This study aims to analyze the species composition and vegetation structure in the succession process in the Natural Recreation Park (NRP) of Kupang District, East Nusa Tenggara Province. Data collection using vegetation analysis on two NRP namely Baumata and Camplong. Research shows that the highest important value index of the seedling level is krinyu (Chromolaena odorata L.) in Baumata NRP (115 %), sapling is johar (Senna siamea) in Camplong NRP (141 %), and for pole and tree are kesambi (Schleichera oleosa, Merr) and jati (Tectona grandis linn. F) on Baumata NRP about 135,5% and 137,1%, respectively. A high value of seedling density indicates that all research location in the succession process.